1993
DOI: 10.1002/ajp.1350310402
|View full text |Cite
|
Sign up to set email alerts
|

Complex leaf‐gathering skills of mountain gorillas (Gorilla g. beringei): Variability and standardization

Abstract: The skills that mountain gorillas use to deal with the stings, tiny hooks, and spines protecting common plant leaves in their diet were examined for variation within and between animals. Many elements of uni-and bimanual performance were identified, often involving delicate precision and coordination, and varying idiosyncratically, each individual having a different set of preferred elements. Many of these elements are functionally equivalent, and all but one weaned animals showed full processing capability; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 21 publications
7
146
0
1
Order By: Relevance
“…Nos últimos anos foram desenvolvidos muitos estudos sobre o uso de ferramentas para a quebra de cocos com macacos-prego em situação de semiliberdade com provisionamento (Ottoni & Mannu, 2001;Resende e Ottoni, 2002;Falótico, 2006;Silva & Ottoni, 2005 as mãos e a boca parece ser uma estratégia de forrageamento importante, comparável ao processamento de frutos de Neesia por orangotangos (van Schaik, 1996) ou de folhas com pelos urticantes, por gorilas (Byrne & Byrne, 1993). Seria interessante verificar se outros grupos de macacos-prego vivendo em ambiente semelhante, que ocorram os frutos descritos …”
Section: Discussionunclassified
“…Nos últimos anos foram desenvolvidos muitos estudos sobre o uso de ferramentas para a quebra de cocos com macacos-prego em situação de semiliberdade com provisionamento (Ottoni & Mannu, 2001;Resende e Ottoni, 2002;Falótico, 2006;Silva & Ottoni, 2005 as mãos e a boca parece ser uma estratégia de forrageamento importante, comparável ao processamento de frutos de Neesia por orangotangos (van Schaik, 1996) ou de folhas com pelos urticantes, por gorilas (Byrne & Byrne, 1993). Seria interessante verificar se outros grupos de macacos-prego vivendo em ambiente semelhante, que ocorram os frutos descritos …”
Section: Discussionunclassified
“…In a more naturalistic setting, Byrne and Byrne (1993;see also Byrne, 1994) investigated both the actions used and the sequences of manipulation in the food processing of mountain gorillas. These authors observed that different plants required different manipulations depending on their natural defenses (e.g., thorns or spines).…”
Section: Simple Relational Problems: Object Manipulationmentioning
confidence: 99%
“…For instance, when eating nettles that are covered with spines, gorillas use both hands, each one performing different actions. Byrne and Byrne (1993) indicated that there was a hierarchical organization in the execution of these manipulations, leading these researchers to postulate that gorillas represented the different steps in the manipulation sequence and executed them as plans. One piece of information that is missing from this naturalistic study is the ontogeny of these manipulations, which could help us understand how the subroutines are established and integrated.…”
Section: Simple Relational Problems: Object Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations have been directed at concept formation (Vonk, 2002(Vonk, , 2003Vonk & MacDonald, 2002), food processing (Byrne & Byrne, 1993;Pika & Tomasello, 2001), learning (Fischer, 1962;Fischer & Kitchener, 1965;Patterson & Tzeng, 1979;Rumbaugh & Steinmetz, 1971;Yerkes, 1927), linguistic skills (Patterson, 1978), mirror self-recognition (InoueNakamura, 1997; Ledbetter & Basen, 1982;Shillito, Gallup, & Beck, 1999;Suarez & Gallup, 1981;Swartz & Evans, 1994), problem-solving (Robbins, Compton, & Howard, 1978), social cognition (e.g., Maestripieri, Ross, & Megna, 2002;Mitchell, 1991;Stoinski, Wrate, Ure, & Whiten, 2001), and tool use (Fontaine, Moisson, & Wickings, 1995;Nakamichi, 1999). Our focus will be only on issues of memory, especially those relevant to the understanding of episodic memory and mental time travel.…”
Section: Introductionmentioning
confidence: 99%